Electrochemical Quality Assurance of Solid Oxide Electrolyser (SOEC) Stacks. Issue 15 (1st November 2019) - Lang, M.; Bohn, C.; Couturier, K.; Sun, X.; McPhail, S. J.; Malkow, T.; Pilenga, A.; Fu, Q.; Liu, Q.
Abstract : High temperature solid oxide cells (SOC) are highly efficient and environmentally friendly electrochemical systems for the H2 /H2 O and/or CO/CO2 redox reactions. The cells can be operated reversely either in electrolysis (SOEC) or fuel cell (SOFC) mode which facilitates this technology for power-to-gas-to-power application in renewable energy storage systems. However, the successful market introduction and public acceptance of the SOEC technology require high quality, reliability and reproducibility of the corresponding cells and stacks. Therefore, in the European funded project "Solid oxide cell and stack testing, safety and quality assurance" (SOCTESQA) pre-normative test modules and programs for high temperature solid oxide cells and stacks have been developed. Different EU project partners have tested identical SOC stacks in several testing campaigns with the same test programs. The paper presents and compares the results of the stacks in SOEC operation which have been obtained by application of the three most important test modules, e.g. current-voltage characteristics, electrochemical impedance spectroscopy and operation at constant current. The results are analyzed and discussed in context to the test input parameters, e.g. gas temperatures and steam supply stability. Quality aspects like repeatability and reproducibility among the different partners and among different test methods are statistically evaluated and discussed.